2015
DOI: 10.1016/j.jcss.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The parameterised complexity of counting connected subgraphs and graph motifs

Abstract: We introduce a family of parameterised counting problems on graphs, p-#Induced Subgraph With Property(Φ), which generalises a number of problems which have previously been studied. This paper focusses on the case in which Φ defines a family of graphs whose edge-minimal elements all have bounded treewidth; this includes the special case in which Φ describes the property of being connected. We show that exactly counting the number of connected induced k-vertex subgraphs in an n-vertex graph is #W[1]-hard, but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 22 publications
0
74
0
Order By: Relevance
“…However, in the case that the number N of witnesses is large, an enumeration algorithm necessarily takes time at least (N ), whereas we might hope for much better if our goal is simply to determine the total number of witnesses. The family of self-contained k-witness problems studied here includes subgraph problems, whose parameterised complexity from the point of view of counting has been a rich topic for research in recent years [10,11,14,[17][18][19]22]. Many such counting problems, including those whose decision problem belongs to FPT, are known to be #W [1]-complete (see [15] for background on the theory of parameterised counting complexity).…”
Section: Application To Countingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case that the number N of witnesses is large, an enumeration algorithm necessarily takes time at least (N ), whereas we might hope for much better if our goal is simply to determine the total number of witnesses. The family of self-contained k-witness problems studied here includes subgraph problems, whose parameterised complexity from the point of view of counting has been a rich topic for research in recent years [10,11,14,[17][18][19]22]. Many such counting problems, including those whose decision problem belongs to FPT, are known to be #W [1]-complete (see [15] for background on the theory of parameterised counting complexity).…”
Section: Application To Countingmentioning
confidence: 99%
“…Positive results in this setting typically exploit structural properties of the graphs involved (e.g. small treewidth) to design (approximate) counting algorithms for inputs with these properties, avoiding any dependence on N [2,3,18].…”
Section: Application To Countingmentioning
confidence: 99%
“…The classes of counting problems we consider fall within the scope of the general model introduced in [11]; this model describes parameterised counting problems in which the goal is to count labelled subgraphs with particular properties. We repeat the definition here for completeness, before extending it to colourful subgraph counting problems (which we will need for intermediate stages in our reductions).…”
Section: The Modelmentioning
confidence: 99%
“…A number of these results concern the complexity of induced subgraph counting problems: Chen and Flum [2] demonstrated that problems of counting k-vertex induced paths and of counting k-vertex induced cycles are both #W [1]-complete, and more generally Chen, Thurley and Weyer [3] showed that it is #W [1]-complete to count the number of induced subgraphs isomorphic to a given graph from the class C (p-#Induced Subgraph Isomorphism(C)) whenever C contains arbitrarily large graphs. Other results concern the complexity of "non-induced" subgraph counting problems, including the problems of counting the number of paths (p-#Path) and cycles (p-#Cycle) [9], matchings (p-#Matching [4]), and connected subgraphs (p-#Connected Induced Subgraph [11]); the well-studied problem of counting the number of k-vertex cliques (p-#Clique [9]) can be considered as either an induced or non-induced subgraph problem. However, even considering these examples, the number of problems known to be complete for the parameterised complexity class #W [1] as a whole remains relatively small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation